Visitor’s perception towards conservation in National Elephant Conservation Centre (NECC), Kuala Gandah, Pahang - Abdullah, Mohd Asyraf (2019)
National Elephant Conservation Centre (NECC) has become one of the popular destinations for eco-tourism. With the availability of various facilities and services provided, visitors who come to the NECC expect the quality of experience gained not to be forgotten. The study aimed to determine the visitors‟ perception towards conservation services provided at the National Elephant Conservation Centre (NECC), Kuala Gandah, Pahang. A total of 255 sets of the questionnaire were distributed to the visitors who already visited the NECC. The study also identified the socio-demographic characteristics of visitors at NECC, Kuala Gandah. Most of the visitors were satisfied with the services in NECC, but the level of satisfaction can be increased if the management of the centre needs to create more activities according to conservation concept that can improve knowledge and awareness among the visitors.